2017
DOI: 10.1002/casp.2297
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Intimate Partner Violence: Towards a Framework for Supporting Effective Community Mobilisation

Abstract: Community mobilisation is a promising new strategy for preventing intimate partner violence (IPV) against women in low-income settings. However, little is known about the contextual factors (e.g. socio-economic, cultural, historical and political conditions) that enable the effective mobilisation of communities for IPV prevention. This paper draws from theoretical work of Campbell and Cornish (2010) on the relationship between context and community action in addressing HIV/AIDS to propose a framework for situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…In following Hedgecoe's thinking of research participants as moral decision-makers we see that the women and men we spoke to had nuanced understandings of the social, cultural and economic factors that perpetuate IPV in their communities. Many were actively involved in trying to address these factors as part of community-based GBV committees (Mannell & Dadswell, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In following Hedgecoe's thinking of research participants as moral decision-makers we see that the women and men we spoke to had nuanced understandings of the social, cultural and economic factors that perpetuate IPV in their communities. Many were actively involved in trying to address these factors as part of community-based GBV committees (Mannell & Dadswell, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…References to such leadership included being unresponsive or able to do 'nothing' on behalf of informally married women who experienced IPV, were denied access to property, or chased away from their homes. Mannell and Dadswell (2017) similarly found that community members rarely mentioned the risks associated with the strategy on behalf of GBV committee members to advise unmarried women to marry their abusers.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Informally married women are disadvantaged in a range of areas including access to property and custody of children, decision-making, social status, and institutional responses to their experiences of IPV. The elevation of formal marital status is so much the case that a proposed solution for informally married women can be to marry their abuser (Mannell and Dadswell, 2017), in order to be in a relationship protective of their rights. A more holistic women's rights agenda, which acknowledges and seeks to address such inequalities is urgently needed in Rwanda.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…A recent study conducted by the University of Rwanda with Oxfam (2017) found that 78.8% of women reported "fear of stigma" as the primary barrier to reporting violence, followed by because an "arrangement between families was made instead" (73.5%), or "feeling that it will change nothing" (65.2%). Given that Rwandan women's poverty and financial dependence on their spouses have been identified as significant barriers to women seeking care, the need to provide integrated health and psychosocial services that support women economically has been strongly emphasized (Russell et al 2016;Umubyeyi et al 2016;Mannell and Dadswell 2017). Supportive community responses to GBV survivors are especially important in Rwanda, given the evidence that men and women are overwhelmingly more likely to ask for help from their neighbors or family members when experiencing physical or sexual violence (NISR 2016).…”
Section: Rwandan Contextmentioning
confidence: 99%